The Efficacy of Reciproc Blue® For Canal Cleanliness Following the Retreatment of Maxillary First Molar: In Vitro Analysis - Mohd Nazrin Isa; Aws Hashim Ali Al-Kadhim; Azlan Jaafar (USIM Press, 2024)
MJoSHT202 1, Volume 7, Issue 1, eISSN: 2601-0003